Psychoacoustic Performance and Music and Speech Perception in Prelingually Deafened Children with Cochlear Implants - Jung, Kyu Hwan (S. Karger AG, 2012)
The number of pediatric cochlear implant (CI) recipients has increased substantially over the past 10 years, and it has become more important to understand the underlying mechanisms of the variable outcomes in this population. In this study, psychoacoustic measures of spectral-ripple and Schroeder-phase discrimination, the Clinical Assessment of Music Perception, and consonant-nucleus-consonant (CNC) word recognition in quiet and spondee reception threshold (SRT) in noise tests have been presented to 11 prelingually deafened CI users, aged 8–16 years with at least 5 years of CI experience. The children's performance was compared to the previously reported results of postlingually deafened adult CI users. The average spectral-ripple threshold (n = 10) was 2.08 ripples/octave. The average Schroeder-phase discrimination was 67.3% for 50 Hz and 56.5% for 200 Hz (n = 9). The Clinical Assessment of Music Perception test showed that the average complex pitch direction discrimination was 2.98 semitones. The mean melody score was at a chance level, and the mean timbre score was 34.1% correct. The mean CNC word recognition score was 68.6%, and the mean SRT in steady noise was −8.5 dB SNR. The children's spectral-ripple resolution, CNC word recognition, and SRT in noise performances were, within statistical bounds, the same as in a population of postlingually deafened adult CI users. However, Schroeder-phase discrimination and music perception were generally poorer than in the adults. It is possible then that this poorer performance seen in the children might be partly accounted for by the delayed maturation in their temporal processing ability, and because of this, the children's performance may have been driven more by their spectral sensitivity.